The Impacts of Cooperative Learning on Oral Proficiency - Talebi, Farima; Sobhani, Atefe (Mediterranean Journal of Social Sciences, 2012)
This study explored whether applying cooperative learning approach brings about significant improvements in Englishlanguage learners' speaking proficiency. 40 male and female students enrolled in a speaking course at IELTS Center institute inMashhad, Iran, were assigned randomly to two control and experimental groups. The administration of an oral interview showed that twogroups were homogeneous in terms of their oral proficiency at the entry level. While both groups received instructions in speaking threesessions per week for one month, CL activities were employed only in the experimental group. The performance of the experimentalgroup on oral interview (posttest) held at the end of the course showed that the mean score of this group was significantly higher thanthe control group. Hence, CL approach can effectively be implemented to improve the learners' speaking proficiency.